Pengaruh Pajak Daerah, Belanja Langsung dan Belanja Tidak Langsung Terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Syarifah Azzahra; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Economic growth is one of the most important indicators in analyzing economic development that occurs in a region or country. Economic growth shows the extent to which economic activity will generate additional income for the community in a certain period. This research aims to look at the influence of regional taxes, direct spending and indirect spending on economic growth in Aceh Province in 2014 - 2023. The data used in this research is secondary data in the form of a time series taken from the last 10 years sourced from the Central Agency. Aceh Province Statistics (BPS) using a quantitative approach. The method used is multiple linear regression analysis. Based on the research results, it can be concluded that Regional Taxes, Direct Expenditures and Indirect Expenditures do not have a significant influence on Economic Growth in Aceh Province in the 2014-2023 period, either individually (separately) or simultaneously (together).